INTERVENTION STRATEGY IN PARENT-FOCUSED PREVENTION TO CHILDREN SEXUAL ABUSE (CSA) : A LITERATURE REVIEW - Annisa Anindita Rahmania; Diva Annisa; Mikha Tiffani; Meita Choppypah; Safarina Kartika Sari (Jurnal Kesehatan Tambusai, 2023)
Sexual violence against children is very common, especially in the global arena. Today the whole country is aware of the danger sexual harassment therefore they take it very seriously. One of them is increasing the participation of parents in preventing these problems. Parents are considered capable of being the main gateway for their children to prevent sexual violence against children. Planting a mindset is not only for children, but also for parents is very important. The main problem when sexual violence against children occurs is the long-term impact that can damage their future. The purpose of this research is to see how strong the changes that occur when interventions are carried out for parents and change the community's perspective on sexual violence against children. The research method is a literature study by filtering several articles into 7 selected articles based on the variables studied. By filtering out articles that have parent respondents who have children aged 7-18 years. This study also found that maximum intervention through counseling and counseling can change perspectives, behavior, and increase the prevention of sexual violence in children massively.